Basque Resultatives and Related Issues - Bavant, Marc (Lingua Posnaniensis, 2013)
Basque has an impressive number of resultative constructions for transitive verbs, not to mention dialectal variants. The purpose of this paper is to classify them according to Nedjalkov’s typology and compare Basque resultatives with similar periphrastic constructions in Classical Armenian. On the way, we meet the questions of Basque diatheses, of voice ambiguity of past participles, and of the affinity between possession and resultativity. The paper is based on material available in the literature and discussions with a native speaker or a specialist of the field. It appears that only “mediopassive”, a detransitivizing transformation, can be considered a diathesis, whereas the so-called “passive” and “antipassive” are respectively an objective and a subjective resultative. Also LAFITTE’S so-called “parfait” (1979) is a resultative, possessive in form and rather subjective in meaning. Classical Armenian displays a strikingly similar series of resultatives and the same kind of voice ambiguity for its past participle. It is hypothesized that the voice ambiguity may be related to the existence of a possessive resultative construction.